Imperfect signals - Georg Graetz (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
A pre-condition for employer learning is that signals at labor market entry do not fully reveal graduates' productivity. I model various distinct sources of signal imperfection - such as noise and multi-dimensional types - and characterize their implications for the private return to skill acquisition. Structural estimates using NLSY data suggest an important role for noise, pushing the private return below the social return. This induces substantial under-investment and causes output losses of up to 22 percent. Value-added-based evidence from Swedish high school graduates also points to noise and under-investment. Highlighting the distinction between schooling duration and skills acquired, I conclude that individuals likely spend too much time in school, but learn too little.
Keywords: D82; I26; J24; J31; 330; Human capital; signaling; employer learning; returns to schooling